Novel Application of a Modified Small T-Plate as an Internal Joint Stabilizer for Chronic Elbow Instability: Technique and Two-Year Results - Wiria Aryanta; Satria Putra Wicaksana (HM Publisher, 2025)
Background: Chronic elbow instability, particularly following neglected or recurrent dislocations, presents a significant treatment challenge. Restoring stability while preserving functional motion is difficult, especially when standard internal joint stabilizers (IJS) are unavailable. We explored the use of a readily available small T-plate, modified intraoperatively, as a temporary internal hinge stabilizer. Case presentation: A 33-year-old male presented with chronic left elbow instability and functional impairment persisting for 14 years after an initial injury. Previous treatments, including traditional bone setting and K-wire fixation, had failed, resulting in recurrent dislocations. Surgical exploration revealed significant fibrosis and compromised ligamentous structures. Open reduction was performed, followed by stabilization using a modified small T-plate contoured to act as an internal hinge, maintaining the ulnohumeral joint space. The implant was removed after 4 weeks. At the 24-month follow-up, the patient exhibited excellent functional outcomes, with a stable elbow, substantial improvement in range of motion (Flexion-extension: 4.2°-129.2°; Pronation-supination: 80°), and an excellent Broberg-Morrey score, enabling pain-free daily activities. Conclusion: This case demonstrated that a modified small T-plate can serve as an effective, low-cost internal hinge joint stabilizer for managing complex chronic elbow instability, particularly in resource-limited settings. It facilitated early controlled motion, promoted stable fibrous tissue healing, and resulted in excellent long-term functional outcomes. This technique presents a viable alternative when standard IJS devices are not accessible.